2013
DOI: 10.4103/0973-029x.110704
|View full text |Cite
|
Sign up to set email alerts
|

An immunohistochemical study of basement membrane heparan sulfate proteoglycan (perlecan) in oral epithelial dysplasia and squamous cell carcinoma

Abstract: Background:Basement membrane heparan sulfate proteoglycan (perlecan) has been demonstrated in precancer lesions and carcinomas of oral cavity. It helps in malignant transformation of epithelial cells. The aim of our study was to understand the immuno-localization of perlecan in oral dysplastic epithelium and oral carcinomas.Materials and Methods:A total of 50 cases comprising 10 normal mucosa, 20 dysplastic mucosa, and 20 oral squamous cell carcinomas (OSCC) were included in the retrospective study. They were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…This molecule is present in all vascularized tissues with a distribution that is primarily confined to basement membranes [17] , [18] . Also, other studies have also identified perlecan in the stromal spaces of various pathophysiological conditions [19] [21] .…”
Section: Introductionmentioning
confidence: 88%
“…This molecule is present in all vascularized tissues with a distribution that is primarily confined to basement membranes [17] , [18] . Also, other studies have also identified perlecan in the stromal spaces of various pathophysiological conditions [19] [21] .…”
Section: Introductionmentioning
confidence: 88%
“…In the breast cancer stroma, the perlecan expression became strong, while it was virtually absent from normal breast stroma. This phenomenon, with deposition of perlecan in the stroma, has been described in other tumours such as colon cancer and oral squamous cell cancer [33,34], and also in wound healing [35]. Perlecan is synthesised in the stroma by both myofibroblasts and cancer cells [36] and due to its proangiogenic properties [37], a high expression of perlecan in the stroma would support new capillary formation during tumour growth.…”
Section: Discussionmentioning
confidence: 78%
“…For antigen retrieval, the deparaffinized sections were kept in staining trough filled with citric acid (2.94 g/L sodium citrate, pH 6.0) and were boiled in pressure cooker for 15 min followed by gradual cooling to 30°C. [ 13 ] The sections were rinsed in 0.01 M phosphate-buffered saline (PBS; 7.4). After that, sections were introduced to peroxide block for 10 min, followed by power block for 10 min, at room temperature in a humidifying chamber.…”
Section: Methodsmentioning
confidence: 99%